Deciphering Investment decision-making: Unraveling Overreaction, Herding and Overconfidence bias through Serial Mediation Analysis - Henry Infant Sebastian PAUL; Natarajan SUNDARAM (International Journal of Computational and Experimental Science and Engineering, 2025)
The current study aims to examine the influence of overreaction on the decision-making processes of investors. Also, this study investigates how herding and overconfidence serially mediate the connection between overreaction and investors’ decision-making. This study used a survey method to collect data using a structured questionnaire from 426 individual investors in the South Indian region. The proposed serial mediation model was analyzed using PLS-SEM. The findings of this study revealed that overreaction significantly affects investors’ decision-making. Herding and overconfidence partially and serially mediate the connection between overreaction and individual investors’ decision-making. These findings contribute to a deeper understanding of biases and their adverse effects on investment decisions, providing crucial insights for investors, financial advisors, and policymakers in the stock market. This study is the first to examine the role of herding and overconfidence in mediating the association between overreaction and the investment decisions of individual investors.